Perception of Dating Style and Extramarital Sex Behavior in Adolescents of University X in Surakarta City - Dzul Fahmi Afriyanto; Wahyu Rizky; Wijayanti Wijayanti (PROMOTOR, 2023)
Adolescence is a time when physical, sexual, psychological, and social changes occur. Adolescence and adolescence are periods of life that range from 10 to 24 years and are risky periods for adolescents. These changes lead adolescents to engage in high-risk behaviors, such as initiation to sexual intercourse, which have important consequences on health. Adolescent girls are at risk of groping/stimulating sensitive body parts during courtship. It also encourages teenagers to engage in sex outside of marriage. The objective is to analyze the perception of dating style towards extramarital sex behavior in adolescents at University X in Surakarta City. This research method uses a qualitative approach, with a case study design. The research informants consisted of the main informants, namely adolescent girls who were students at University X in Surakarta City. The results showed that the majority of adolescent girls' dating style by meeting in person and communicating via WhatsApp. Informants feel sexual attraction or urges when dating. The perception of adolescent vulnerability is high and the perception of seriousness is high to the dangers and impacts of extramarital sex. Adolescents who have a perception of benefits and perceptions of obstacles in dating behavior and sex outside marriage are beneficial, tend to have more encouragement in engaging in extramarital sex acts. Adolescents have confidence and cues to behave in dating and extramarital sex, so they are encouraged to consistently engage in these behaviors.